2002
DOI: 10.1038/sj.bmt.1703574
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and T cell costimulatory blockade as post-transplant treatment promote fully MHC-mismatched allogeneic bone marrow engraftment under irradiation-free conditioning therapy

Abstract: Summary:Hematopoietic macrochimerism, established by bone marrow transplantation, can be used as an approach for treating autoimmune disease and inducing transplant tolerance. In this study, we investigated whether a stable, high level of fully MHC-mismatched hematopoietic macrochimerism can be induced by using irradiation-free protocols, and whether rapamycin and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
(32 reference statements)
2
19
1
Order By: Relevance
“…By contrast, under the relatively stringent conditions used in our studies (no irradiation, no donor-specific transfusion, single busulfan treatment, and single BM cell transfer), the combination of anti-CD40L and everolimus was strictly synergistic, as neither reagent alone supported chimerism upon BMTx. This contrasts with reports on BMTx-induced chimerism under CD40L blockade alone, presumably owing to stronger cytoreduction or repeated BM infusion with more frequent administration of anti-CD40L (12,56,57). Several mechanisms of action were proposed for anti-CD40L, as a single agent or in combination with CTLA4Ig or rapamycin, including the induction of T regulator cells (58,59), Fc-and complement-dependent deletion (60,61), and apoptosis through costimulation blockade (10,62,63).…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…By contrast, under the relatively stringent conditions used in our studies (no irradiation, no donor-specific transfusion, single busulfan treatment, and single BM cell transfer), the combination of anti-CD40L and everolimus was strictly synergistic, as neither reagent alone supported chimerism upon BMTx. This contrasts with reports on BMTx-induced chimerism under CD40L blockade alone, presumably owing to stronger cytoreduction or repeated BM infusion with more frequent administration of anti-CD40L (12,56,57). Several mechanisms of action were proposed for anti-CD40L, as a single agent or in combination with CTLA4Ig or rapamycin, including the induction of T regulator cells (58,59), Fc-and complement-dependent deletion (60,61), and apoptosis through costimulation blockade (10,62,63).…”
Section: Discussioncontrasting
confidence: 46%
“…Rapamycin/sirolimus was recently shown to induce hemopoietic chimerism in combination with anti-CD40L, albeit in the context of more permissive protocols that also supported chimerism with rapamycin or anti-CD40L alone (57) or with CD40L blockade alone (58). By contrast, under the relatively stringent conditions used in our studies (no irradiation, no donor-specific transfusion, single busulfan treatment, and single BM cell transfer), the combination of anti-CD40L and everolimus was strictly synergistic, as neither reagent alone supported chimerism upon BMTx.…”
Section: Discussionmentioning
confidence: 99%
“…Since we previously found that co-stimulatory blockade and rapamycin after BMT can enhance the induction of mixed chimerism (14), we hypothesized that shortterm post-transplant treatment with anti-CD154 mAb and rapamycin could suppress host-versus-graft response and promote the induction of donor chimerism under a less-intensive conditioning therapy. First, we investigated whether donor chimerism could be induced in the MHCmismatched BALB/c to C57BL/6 mouse combination by a relatively non-toxic conditioning therapy; and whether short-term post-transplant treatment with anti-CD154 mAb and rapamycin could enhance donor chimerism under cy- clophosphamide alone as conditioning therapy.…”
Section: Resultsmentioning
confidence: 99%
“…As regards allogeneic and, especially, xenogeneic transplantations, BU alone is not enough for a pretreatment regimen, and some additional immunosuppressive therapy must be perfomed [6,107,152,161]. The most frequently applied protocols include myeloablative agents in combination with CY or other immunosuppressive drugs, depending on the type of transplantation [29,158].…”
Section: Pretreatment Regimens Used In the Mouse Hsct Modelsmentioning
confidence: 99%
“…These regimens are usually much milder than the "classical" ones [1,116,129]. The most interesting directions of research are the new analogs of known immunosuppressive and myeloablation agents [152], costimulatory blockade [1,8,97,151], and different combinations of supra-lethal doses of irradiation and/or chemotherapeutic drugs [52,61,62,69,158]. Induction of alloantigenprimed lymphocyte depletion was recently documented to be an effective method for tolerance induction across MHC using non-myeloablative conditioning as well [93].…”
Section: Pretreatment Regimens Used In the Mouse Hsct Modelsmentioning
confidence: 99%